Sedimentary records of polychlorinated biphenyls in the East China Marginal Seas and Great Lakes: Significance of recent rise of emissions in China and environmental implications. (November 2019) - Wu, Zilan; Lin, Tian; Li, An; Zhou, Shanshan; He, Huan; Guo, Jiehong; Hu, Limin; Li, Yuanyuan; Guo, Zhigang
Abstract: Polychlorinated biphenyls (PCBs) in dated sediment cores from the East China Marginal Seas (ECMSs) and the chronology of the net fluxes to sediments were analyzed. The accumulation of 27 PCBs (ΣPCBs) in the ECMS sediments is about 5–26 ng cm −2, with the net depositional fluxes of ΣPCBs 10 times lower than those observed in the Great Lakes during the 1960s–1970s. Exponential increases in PCB deposition to the ECMS sediments since the 1990s were observed, which closely follows the fast growth of PCB emissions from industrial thermal processes and e-waste related sources in China. Recent PCB fluxes to the study sites in the ECMSs and the Great Lakes are comparable; the former surged forward with a rising tendency, while the latter showed continued decline after the late 1970s. Due to the different PCB application histories and sources between the two regions, the ECMS sediments may remain as a net sink for land-derived PCBs, while sediments in the Great Lake may have been acting as a secondary source releasing PCBs to water. A higher proportion of trichlorobiphenyls in the ECMS sediments than the Great Lakes was indicated, which may imply the net transport of atmospheric PCBs from China. Graphical abstract: Image 1 Highlights: The chronology of PCB fluxes to sediments of the ECMSs and the Great Lakes differed in recent decades. Recent increases in PCB deposition to the sediment of the ECMSs closely follows the economic growth in China. Fate processes are divergent with respect to sediment PCBs in the ECMSs and the Great Lakes. Abstract : Different effects of regional historical usage and emerging emissions on fate and transport of sediment PCBs in global environment were indicated by tracking the historical and recent environmental pollution of PCBs in China and industrialized North America.